Discipline analysis of Pattimura University graduates in education units in the Maluku islands - Ritiauw, Samuel Patra; Salamor, Lisye (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
The condition of Maluku with geographical aspects also determines the existence of teacher resources. This research aims to determine the character of teacher discipline in education units in the archipelago. Using mixed research methods, a quantitative approach with a Likert scale and qualitative research with a phenomenological approach, the research location is in Central Maluku, West Seram and Southwest Maluku districts. The population and research sample were teachers who graduated from Pattimura University. The research sample consisted of principals in the islands, resource persons who were principals, vice principals of elementary, junior high, high school, and vocational schools, and community leaders. Data collection techniques were conducted using questionnaires, interviews, and observations. The research results were analysed statistically, and qualitative data was analysed through data reduction, data presentation, conclusion drawing and verification.  Furthermore, the study's results provide an overview of the character of teacher discipline in the education units at the research locations, which is slightly different. Southwest Maluku District <70% and Central Maluku District <80%. Data from interviews and observations also support this data that natural conditions significantly affect the presence of teachers in education units and curriculum development in units in the Maluku Islands.